Black shank-mediated alteration of the community assembly of rhizosphere soil bacteria in tobacco - Ma, Junchi; Chen, Jili; Zhang, Qing; Dong, Yumei; Li, Zhihua; Xie, Junqiu; Yang, Dongmei; Zhou, Lequn; Yan, Dahao; Zhou, Bo; Liu, Tao (Frontiers in Microbiology, 2024)
There is a close and complex interaction between the elements in the aboveground-underground ecosystem during the growth and development of plants. Specifically, when the aboveground part of plants is infected by pathogens, it induces the plant rhizosphere to synthesize specific root exudates. Consequently, a group of beneficial rhizosphere soil bacteria is recruited to help plants resist diseases. However, the changes in the rhizosphere soil bacterial community of plants under infection by oomycete pathogens remain unknown. This study demonstrates that tobacco plants recruit microorganisms at the rhizosphere level as a defense mechanism against disease after infection by the oomycete pathogen Phytophthora nicotianae. Specific rhizosphere soil bacteria were screened in vitro to promote tobacco growth in a biofilm-forming manner, which induced the systemic resistance of the plants to P. nicotianae. The recruitment of rhizosphere soil bacteria to the inter-root zone of tobacco plants after infection by P. nicotianae can help subsequently cultivated tobacco plants in the same soil resist pathogen infestation. In conclusion, the present study confirms that infestation caused by oomycete pathogens alters the composition of the plant rhizosphere soil bacterial community and recruits a specific group of beneficial microorganisms that induce disease resistance and promote plant growth, thereby maximizing the protection of progeny grown in the same soil against the disease.